Impact of COVID-19 for people living and working with ADHD: A brief review of the literature - Jack Hollingdale (AIMS Press, 2021)
Objective: COVID-19 lockdowns have changed the social and environmental context. Those with ADHD are more vulnerable to experiencing difficulties than their non-ADHD peers. This paper attempts to provide a brief summary of the literature that has emerged during the COVID-19 pandemic.